A method of encapsulating carbon material with sulfonated polymer for photo-thermal catalysis
Patent Information
- Application Number
- CN202511924610.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-19
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]本发明专利的目的是解决传统催化及热源辅助光热反应体系面临的反应效率低、能耗高的瓶颈问题,提供一种磺化聚合物封装碳材料光热催化果糖转化的方法,磺化聚合物封装碳材料的催化效果远高于现有催化体系,显著降低了能耗
[0012] The beneficial effects of this invention are as follows: 1) A new photothermal catalyst was designed and applied to liquid-phase reactions, namely, catalyzing the dehydration of fructose in ethanol or DMSO to prepare HMF or EMF, which showed good photothermal catalytic performance under both xenon lamp light source and natural sunlight conditions; 2) The structure of this catalyst reduces the rate at which the catalyst dissipates heat into the solvent, especially achieving a high yield of HMF under natural sunlight, and the HMF generation rate per unit mass of catalytic system per unit time is higher than that in existing literature; 3) The catalyst preparation method is simple and the required raw materials are inexpensive, which may have great commercial potential.
Smart Images

Figure CN122912914A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for encapsulating carbon materials with sulfonated polymers for photothermal catalysis, belonging to the field of biomass-based chemicals. Background Technology
[0002] Existing research confirms that gradually replacing fossil resources with renewable lignocellulosic biomass is a key pathway to achieving sustainable development. Among these, the synthesis of 5-hydroxymethylfurfural (HMF) from hexoses is crucial for establishing a biomass refining technology system. Although the reported HMF yields are relatively high, the HMF generation rate per unit mass of catalytic system per unit time remains low. Consequently, existing catalytic systems can only convert low substrate concentrations, leading to high energy consumption and high carbon emissions. Increasing substrate loading often exacerbates side reactions, while optimizing reaction conditions is limited by energy consumption costs. Therefore, developing novel reaction systems that combine high catalytic efficiency with low energy consumption is a key direction for overcoming the bottlenecks in the industrialization of biomass conversion technology.
[0003] If the excellent photothermal conversion capability and catalytic conversion capability of catalysts can be integrated, solar-driven catalytic conversion will provide new impetus for many energy-intensive reactions. Photothermal catalysis strategies have shown outstanding performance in some gas-phase reactions, including important reactions such as carbon dioxide hydrogenation, ammonia decomposition, formic acid decomposition to carbon monoxide, methanol steam reforming, and Fischer-Tropsch synthesis under high-temperature conditions. In contrast, high-energy-consuming or low-efficiency liquid-phase reactions require the establishment of efficient photothermal catalytic systems. However, the heat generated by photothermal catalysts in liquid-phase reaction systems is rapidly conducted to the solvent medium and ultimately dissipated to the surrounding environment through the reaction system. In known cases of photothermal catalytic biomass conversion, such as acid-catalyzed sugar dehydration to HMF and lignin hydrogenolysis, both require simultaneous external auxiliary heating and light irradiation, resulting in high energy consumption and low efficiency. Therefore, photothermal catalysts designed for liquid-phase catalytic reactions must not only have the active sites of traditional catalysts but also improve photothermal conversion efficiency and heat utilization efficiency.
[0004] To address the problems of high energy consumption and low efficiency in traditional thermocatalysis, this invention designs a highly efficient photothermal catalyst. It utilizes carbon materials to absorb light and generate heat, employs polymers containing sulfonic acid groups for catalytic action, and further utilizes the polymers wrapped around carbon nanotubes to reduce heat loss, thereby improving photothermal conversion efficiency. This catalyst exhibits excellent catalytic performance under both artificial light and natural sunlight irradiation conditions. Summary of the Invention
[0005] The purpose of this invention is to solve the bottleneck problems of low reaction efficiency and high energy consumption faced by traditional catalytic and heat source-assisted photothermal reaction systems, and to provide a method for photothermal catalysis of fructose conversion using sulfonated polymer-encapsulated carbon materials. The catalytic effect of sulfonated polymer-encapsulated carbon materials is far superior to that of existing catalytic systems, and energy consumption is significantly reduced.
[0006] A method for encapsulating carbon materials with sulfonated polymers for photothermal catalysis, the invention mainly includes: (1) Preparation of polymer-encapsulated carbon material, including the following steps: Step 1, dissolving monomers: Add a certain volume of tetrahydrofuran and water to the lining of the polytetrafluoroethylene reactor, and add the weighed sodium p-styrene sulfonate to the solvent under stirring conditions.
[0007] Step 2, introduce crosslinking agent: add divinylbenzene after sodium styrene sulfonate has completely dissolved.
[0008] Step 3, Add carbon material: After sodium styrene sulfonate and divinylbenzene are mixed evenly, add carbon material.
[0009] Step 4, Add initiator: After stirring for a certain period of time, add the initiator azobisisobutyronitrile; Step 5, start the reaction: After stirring for a certain period of time, remove the rotor and put the polytetrafluoroethylene liner into the reactor. Perform a hydrothermal reaction at 100°C for 24 hours. Step 6, Cleaning and drying the material: After the reaction is complete, wash the material 5 times with methanol, 5 times with 1 mol / L sulfuric acid solution, and then wash it 5 times with methanol. Dry it under vacuum at 80℃ for 24 h. Finally, grind the solid material into powder, which is the catalyst.
[0010] (2) Catalytic effect test of polymer-encapsulated carbon materials Catalytic preparation of 5-hydroxymethylfurfural (HMF) from fructose in dimethyl sulfoxide: 4 parts polymer-encapsulated carbon material, 9-200 parts fructose, 220 parts dimethyl sulfoxide, light intensity 500-2100 mW / cm² 2 The reaction time is 5–120 minutes. After the reaction, the solution is diluted with water, filtered, and then placed into a sample vial. HMF is determined by high-performance liquid chromatography equipped with a UV detector; the mobile phase is a mixture of methanol and water (V / V). 甲醇 V 水 = 60:40), column temperature 30℃. Fructose concentration was determined by high performance liquid chromatography equipped with a parallax detector, mobile phase 5 mM H2SO4, column temperature 35℃.
[0011] Catalytic preparation of 5-ethoxymethylfurfural (EMF) and 5-hydroxymethylfurfural (HMF) from fructose in ethanol: 4 parts polymer-encapsulated carbon material, 9 parts fructose, 160 parts anhydrous ethanol; light intensity 900–1400 mW / cm².2 The reaction time is 30–210 minutes. After the reaction, the solution is diluted with water, filtered, and then placed into a sample vial. EMF and HMF are determined by high-performance liquid chromatography equipped with a UV detector, using a mixture of methanol and water as the mobile phase (V). 甲醇 V 水 = 60:40), column temperature 30℃. Fructose concentration was determined by high performance liquid chromatography equipped with a differential detector, mobile phase 5 mM H2SO4, column temperature 35℃.
[0012] The beneficial effects of this invention are as follows: 1) A new photothermal catalyst was designed and applied to liquid-phase reactions, namely, catalyzing the dehydration of fructose in ethanol or DMSO to prepare HMF or EMF, which showed good photothermal catalytic performance under both xenon lamp light source and natural sunlight conditions; 2) The structure of this catalyst reduces the rate at which the catalyst dissipates heat into the solvent, especially achieving a high yield of HMF under natural sunlight, and the HMF generation rate per unit mass of catalytic system per unit time is higher than that in existing literature; 3) The catalyst preparation method is simple and the required raw materials are inexpensive, which may have great commercial potential. Attached Figure Description
[0013] Figure 1 (a) Schematic diagram of the synthesis of catalyst SPSS / DVB / CNT; (b) Scanning electron microscope (SEM) images of CNT, (c) CNT-SO3H, and (d) SPSS / DVB / CNT; (e) CNT, (f) CNT-SO3H, (g) SPSS / DVB, and (h) Transmission electron microscope (TEM) images of SPSS / DVB / CNT; (i) HAADF image and EDS elemental distribution map of SPSS / DVB / CNT.
[0014] Figure 2 (a) Raman spectra, (b) pore size distribution, (c) infrared spectra, and (d) thermogravimetric curves of catalysts CNT, CNT-SO3H, SPSS / DVB, and SPSS / DVB / CNT; (e) XPS fitting peak diagrams of S2p and O1s of catalysts CNT-SO3H and SPSS / DVB / CNT.
[0015] Figure 3 (a) UV-Vis and NIR absorption spectra of CNT, CNT-SO3H, and SPSS / DVB / CNT; (b) 100 mW / cm 2 Infrared images of the initial and maximum temperatures of CNT-SO3H and SPSS / DVB / CNT in air under light intensity conditions; (c) 100 mW / cm 2Temperature change process of CNT, CNT-SO3H, and SPSS / DVB under light intensity conditions (d) Schematic diagram of temperature response of CNT-SO3H and SPSS / DVB / CNT.
[0016] Figure 4 Between 500 and 1100 mW / cm 2 (a) Temperature change of the DMSO-SPSS / DVB / CNT reaction system under light intensity conditions; (b) Fructose conversion rate under SPSS / DVB / CNT catalysis; (c) Yield under SPSS / DVB / CNT catalysis; 1100 mW / cm 2 The effects of fructose dosage on yield under the following conditions: (d) yield under air atmosphere with different catalysts; (e) yield under nitrogen atmosphere with different catalysts.
[0017] Figure 5 At (a) 1600 mW / cm 2 (b) 1900 mW / cm 2 and (c) 2100 mW / cm 2 Photothermal reaction rate under light intensity. Reaction conditions: 1000 mg fructose, 20 mg catalyst, 1 mL DMSO.
[0018] Figure 6 Reaction rates under heating conditions of (a) 113℃, (b) 127℃, and (c) 137℃. Reaction conditions: 1000 mg fructose, 20 mg catalyst, 1 mL DMSO, oil bath heating.
[0019] Figure 7 (a) Activation energy of thermocatalytic and photothermal systems (b) Thermal field simulation of catalyst SPSS / DVB / CNT in DMSO (c) Thermal field distribution of SPSS / DVB / CNT and CNT-SO3H along the Y-axis (d) Schematic diagram of the reaction mechanism of SPSS / DVB / CNT as a photothermal catalyst.
[0020] Figure 8 900–1400 mW / cm 2 (a) Temperature change of the fructose-ethanol-SPSS / DVB / CNT reaction system under light intensity conditions; (b) Fructose conversion rate under SPSS / DVB / CNT catalysis; (c) Yield under SPSS / DVB / CNT catalysis; 1200 mW / cm 2 (d) Temperature changes of different reaction systems under different conditions, (e) Fructose conversion rate under different catalysts, and (f) Yield under different catalysts.
[0021] Figure 9 (a) Simple outdoor photothermal catalytic reaction device; (b) HMF yield, fructose conversion rate, and temperature change of the DMSO-SPSS / DVB / CNT reaction system after 10 minutes of reaction under natural outdoor sunlight; (c) Comparison of HMF generation rate per unit mass of catalytic system per unit time in the photothermal system of this invention with existing literature.
[0022] Figure 10 2100 mW / cm 2 Yield under SPSS / DVB / CNT catalysis under specific light intensity conditions. Reaction conditions: 500 mg inulin; 20 mg catalyst, 1 mL DMSO.
[0023] Figure 11 1900 mW / cm 2 Yield under SPSS / DVB / CNT catalysis under light intensity conditions. Reaction conditions: 10 mg glucose; 20 mg SPSS / DVB / CNT, 50 mg SnP, 1 mL DMSO.
[0024] Figure 12 Yield under SPSS / DVB / CB catalysis at 1100 mW / cm² light intensity. Reaction conditions: 45 mg fructose; 20 mg catalyst, 1 mL DMSO. Detailed Implementation
[0025] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to embodiments. The content mentioned in the embodiments is not intended to limit the present invention. Example
[0026] This invention discloses a method for encapsulating carbon materials with sulfonated polymers for photothermal catalysis, comprising the following steps: (1) First, the sulfonated polymer-encapsulated carbon nanotube catalyst was synthesized: 3.2 g of sodium p-styrene sulfonate was dissolved in 19.6 mL of tetrahydrofuran and 4.5 mL of deionized water; after the sodium p-styrene sulfonate was completely dissolved, 0.4 g of carbon nanotubes were added and stirred at room temperature for 5 min; 2.0 g of divinylbenzene was added and stirred at room temperature for 5 min; 0.055 g of azobisisobutyronitrile was added and stirred for 20 min. The rotor was removed and the polytetrafluoroethylene liner was placed in the reactor; the reaction was carried out at 100℃ for 24 h; after the reaction was completed, the material was washed 5 times with methanol, 5 times with 1 mol / L sulfuric acid solution, and then washed 5 times with methanol. The material was dried under vacuum at 80℃ for 24 h. The solid material was ground into powder to obtain the sulfonated polymer-encapsulated carbon nanotube catalyst, named SPSS / DVB / CNT.
[0027] (2) Comparative catalyst 1: p-aminobenzenesulfonic acid sulfonated carbon nanotubes, prepared as follows: 150 mL of deionized water and 1.0 g of carbon nanotubes were added to a round-bottom flask, stirred and heated under reflux at 80 °C, 2.0 g of p-aminobenzenesulfonic acid was added and stirred for 0.5 h, then 2.0 g of isoamyl nitrite was added, and the mixture was reacted at 80 °C for 12 h. The product was collected by filtration, washed successively with water, DMF (N,N-dimethylformamide) and methanol, and then dried at 80 °C for 12 h. Finally, the solid material was ground into powder, which is the comparative catalyst p-aminobenzenesulfonic acid sulfonated carbon nanotubes, named CNT-SO3H.
[0028] (3) Comparative catalyst 2: sulfonated resin. The preparation process of sulfonated resin is as follows: 19.6 mL of tetrahydrofuran and 4.5 mL of water were added to the polytetrafluoroethylene liner. After stirring evenly, 2 g of divinylbenzene, 3.2 g of sodium p-styrene sulfonate and 0.055 g of azobisisobutyronitrile were added. After covering the container, the mixture was magnetically stirred at room temperature and hydrothermally reacted at 100°C for 24 h. After the reaction was completed, the material was washed 5 times with methanol, 5 times with 1 mol / L sulfuric acid solution, and then washed 5 times with methanol. The mixture was vacuum dried at 80°C for 24 h. Finally, the solid material was ground into powder, which is the comparative catalyst sulfonated resin, named SPSS / DVB.
[0029] (4) Comparison catalyst 3: carbon nanotubes (CNTs).
[0030] (5) Reaction system: 20 mg catalyst (SPSS / DVB / CNT, CNT-SO3H, SPSS / DVB, CNT), 1 mL DMSO, fructose concentration 3.9-47.6%, reaction light intensity 500-2100 mW / cm 2 The reaction time is 5 to 120 minutes.
[0031] (6) After the reaction, dilute with water 5000–10000 times, filter, and then fill into a sample vial. HMF is determined by high-performance liquid chromatography equipped with a UV detector, with a mobile phase of a mixture of methanol and water (V0.05). 甲醇 V 水 = 60:40), column temperature 30℃. Fructose concentration was determined by high performance liquid chromatography equipped with a parallax detector, mobile phase 5 mM H2SO4, column temperature 35℃.
[0032] (7) The catalysts SPSS / DVB / CNT, CNT-SO3H, SPSS / DVB, and CNT were characterized by SEM and TEM, see below. Figure 1 .
[0033] (8) The catalysts SPSS / DVB / CNT, CNT-SO3H, SPSS / DVB, and CNT were characterized in terms of structure, elemental groups, and thermal stability. See below. Figure 2 .
[0034] (9) The photothermal properties of the catalysts SPSS / DVB / CNT, CNT-SO3H, SPSS / DVB, and CNT were tested in an air environment, see [see details]. Figure 3 .
[0035] (10) In the range of 500 to 1100 mW / cm 2 The photothermal catalytic effects of CNT, CNT-SO3H, SPSS / DVB, and CNT were tested under different light intensities. (See attached image.) Figure 4 .
[0036] (11) At 1600, 1900 and 2100 mW / cm 2 The reaction rates of the photothermal system under different light intensities and the corresponding reaction rates of the thermocatalytic system at apparent temperatures of 113, 127, and 137 °C are shown below. Figure 5 , Figure 6 .
[0037] (12) The mechanism of the excellent catalytic performance of the photothermal catalyst SPSS / DVB / CNT is described in Figure 7 .
[0038] (10) Characterization results showed that CNT-SO3H and CNT had similar basic morphologies. SPSS / DVB showed rough, fine particles, but SPSS / DVB / CNT particles were larger. TEM images of SPSS / DVB / CNT sections showed that carbon nanotubes were wrapped and encapsulated by polymers. HAADF and EDS images showed that C, O, and S elements were uniformly dispersed in the catalyst SPSS / DVB / CNT. Raman spectroscopy results of the catalyst SPSS / DVB / CNT showed that the D and G band peaks were very weak, and its I band peaks were very weak. d / I g The values are closer to those of the SPSS / DVB catalyst; while CNT-SO3H and CNT show obvious D and G band peaks. The specific surface area of the SPSS / DVB / CNT catalyst is between that of CNT and SPSS / DVB, but its pore size distribution is very similar to that of SPSS / DVB. Infrared and XPS characterization patterns show that all three catalysts, CNT-SO3H, SPSS / DVB, and SPSS / DVB / CNT, contain sulfonic acid groups, with sulfonic acid amounts of 3.1, 2.4, and 2.3 mmol g, respectively. -1 Thermogravimetric analysis showed that SPSS / DVB / CNT had better thermal stability than CNT-SO3H.
[0039] (11) Studies on photothermal properties show that, except for the polymer SPSS / DVB, the other catalysts have high light absorption rates across the entire spectrum. In air, the absorption rate is 100 mW / cm². 2 Under light intensity irradiation, CNTs exhibited the fastest heating rate, but the equilibrium temperature of SPSS / DVB / CNTs was comparable to that of CNTs, significantly higher than that of CNT-SO3H. After the light source was turned off, the cooling rate of CNTs was faster than that of SPSS / DVB / CNTs, indicating that the encapsulation structure of SPSS / DVB / CNTs reduced the heat dissipation rate. The results are shown below. Figure 3 .
[0040] (12) The experimental results of catalytic effect show that 1100 mW / cm 2 In a fructose-DMSO system at 45 g / L, the HMF yield of SPSS / DVB / CNT was 90.3%; in a fructose system at 500 g / L, the HMF yield of SPSS / DVB / CNT remained as high as 78.9%, demonstrating superior performance compared to existing literature. SPSS / DVB / CNT and CNT-SO3H exhibited good catalytic performance under both nitrogen and air atmospheres; however, the HMF yield of the other two catalysts decreased significantly under nitrogen conditions, and their catalytic effects were not observed. Figure 4 .
[0041] (13) At 1600, 1900 and 2100 mW / cm 2 Under different light intensities, the generation rates of HMF were 7.4, 8.1, and 8.6 mmol / L g. -1 h -1 (See Figure 5 The reaction systems corresponded to apparent temperatures of 113, 127, and 137 °C. Under thermocatalytic conditions, the HMF formation rates at heating temperatures of 113, 127, and 137 °C were 3.0, 3.5, and 3.9 mmol / L g, respectively. -1 h -1 (See Figure 6 Based on the results of the relationship between temperature and reaction rate (see...) Figure 7 The activation energy of the photothermal catalyst system (8.3 kJ / mol) was significantly lower than that of the thermocatalytic system (14.4 kJ / mol). –1This further confirms that the photothermal system is superior to the traditional thermocatalytic system. At the nanoscale, the photothermal catalyst and the reaction solution exchange heat to form a temperature gradient region. Catalytic experiments and COMSOL multiphysics simulations show that both SPSS / DVB / CNT and CNT-SO3H form a gradient temperature region between the catalyst and the solution interface. Infrared temperature recorder data shows that the apparent maximum temperature of SPSS / DVB / CNT is 10°C higher than that of CNT-SO3H. COMSOL multiphysics simulations also show that the peak temperature at the interface between the catalyst SPSS / DVB / CNT and the solvent is 20°C higher than that of CNT-SO3H. Therefore, the former is more likely to generate a high-temperature localized thermal field, further demonstrating that the encapsulation structure of SPSS / DVB / CNT effectively reduces heat dissipation into the environment.
[0042] Both SPSS / DVB / CNT and CNT-SO3H catalysts contain Brønsted acid and have porous structures, enabling them to effectively drive acid-catalyzed reactions as thermal catalysts. These two catalysts can effectively convert light energy into a high localized thermal field, significantly higher than the solution's own temperature. However, in conventional thermocatalysis, the heat transfer process is from heat source-reactor-solution-catalyst, thus the temperature of the catalyst's active site is lower than or close to the solution temperature. At the same apparent temperature, the photothermal reaction rate is significantly higher than the thermocatalytic reaction rate, thereby reducing side reactions and achieving a higher HMF yield. The main difference between SPSS / DVB / CNT and other photothermal catalysts is its unique encapsulation structure, which facilitates slow heat transfer into the solution, resulting in higher temperatures and faster reaction rates. The superior catalytic performance of SPSS / DVB / CNT is attributed to its ingenious integration of acid active sites and photothermal conversion capabilities into the encapsulation structure, thereby inducing a local high-temperature gradient to drive the reaction. Example
[0043] This invention discloses a method for encapsulating carbon materials with sulfonated polymers for photothermal catalysis, comprising the following steps: (1) First, the sulfonated polymer-encapsulated carbon nanotube catalyst was synthesized: 3.2 g of sodium p-styrene sulfonate was dissolved in 19.6 mL of tetrahydrofuran and 4.5 mL of deionized water; after the sodium p-styrene sulfonate was completely dissolved, 0.4 g of carbon nanotubes were added and stirred at room temperature for 5 min; 2.0 g of divinylbenzene was added and stirred at room temperature for 5 min; 0.055 g of azobisisobutyronitrile was added and stirred for 20 min. The rotor was removed and the polytetrafluoroethylene liner was placed in the reactor; the reaction was carried out at 100℃ for 24 h; after the reaction was completed, the material was washed 5 times with methanol, 5 times with 1 mol / L sulfuric acid solution, and then washed 5 times with methanol. The material was dried under vacuum at 80℃ for 24 h. The solid material was ground into powder to obtain the sulfonated polymer-encapsulated carbon nanotube catalyst, named SPSS / DVB / CNT.
[0044] (2) Comparative catalyst 1: p-aminobenzenesulfonic acid sulfonated carbon nanotubes, prepared as follows: 150 mL of deionized water and 1.0 g of carbon nanotubes were added to a round-bottom flask, stirred and heated under reflux at 80 °C, 2.0 g of p-aminobenzenesulfonic acid was added and stirred for 0.5 h, then 2.0 g of isoamyl nitrite was added, and the mixture was reacted at 80 °C for 12 h. The product was collected by filtration, washed successively with water, DMF (N,N-dimethylformamide) and methanol, and then dried at 80 °C for 12 h. Finally, the solid material was ground into powder, which is the comparative catalyst p-aminobenzenesulfonic acid sulfonated carbon nanotubes, named CNT-SO3H.
[0045] (3) Comparative catalyst 2: sulfonated resin. The preparation process of sulfonated resin is as follows: 19.6 mL of tetrahydrofuran and 4.5 mL of water were added to the polytetrafluoroethylene liner. After stirring evenly, 2 g of divinylbenzene, 3.2 g of sodium p-styrene sulfonate, and 0.055 g of azobisisobutyronitrile were added. After covering the container, the mixture was magnetically stirred at room temperature and hydrothermally reacted at 100°C for 24 h. After the reaction was completed, the material was washed 5 times with methanol, 5 times with 1 mol / L sulfuric acid solution, and then washed 5 times with methanol. The mixture was vacuum dried at 80°C for 24 h. Finally, the solid material was ground into powder, which is the comparative catalyst sulfonated resin, named SPSS / DVB.
[0046] (4) Comparison catalyst 3: carbon nanotubes (CNT).
[0047] (5) Reaction system: 20 mg catalyst (SPSS / DVB / CNT, CNT-SO3H, SPSS / DVB, CNT), 1 mL anhydrous ethanol, fructose concentration 3.9%, reaction light intensity 900-1400 mW / cm 2 The reaction time is 30 to 210 minutes.
[0048] (6) After the reaction, dilute with water 500 times, filter, and then put into a sample vial. HMF and EMF are determined by high-performance liquid chromatography equipped with a UV detector, with a mobile phase of a mixture of methanol and water (V). 甲醇 V 水 = 60:40), column temperature 30℃. Fructose concentration was determined by high performance liquid chromatography equipped with a parallax detector, mobile phase 5 mM H2SO4, column temperature 35℃.
[0049] (7) The catalysts SPSS / DVB / CNT, CNT-SO3H, SPSS / DVB, and CNT were characterized by SEM and TEM, see below. Figure 1 .
[0050] (8) The catalysts SPSS / DVB / CNT, CNT-SO3H, SPSS / DVB, and CNT were characterized in terms of structure, elemental groups, and thermal stability. See below. Figure 2 .
[0051] (9) The photothermal properties of the catalysts SPSS / DVB / CNT, CNT-SO3H, SPSS / DVB, and CNT were tested in an air environment, see [see details]. Figure 3 .
[0052] (10) In the range of 900–1400 mW / cm 2 The photothermal catalytic effects of CNT, CNT-SO3H, SPSS / DVB, and CNT were tested under different light intensities.
[0053] (11) Catalytic effect experiments showed that the catalyst SPSS / DVB contains acidic sites but has very weak light absorption; CNT has strong photothermal generation ability but does not contain catalytically active sites. Therefore, the catalytic activity of SPSS / DVB and CNT under light conditions is very low. The catalytic activity of SPSS / DVB / CNT and CNT-SO3H under light conditions was compared in the range of 900–1400 mW / cm². 2 Catalytic effect of fructose-ethanol solution system under light intensity; catalyst SPSS / DVB / CNT at 1200 mW / cm 2 The EMF yield and HMF / EMF total yield were 67.1% and 73.7%, respectively, which were higher than those of CNT-SO3H (59.1% and 64.4%). (See experimental results below.) Figure 8 . Example
[0054] This invention discloses a method for encapsulating carbon materials with sulfonated polymers for photothermal catalysis, comprising the following steps: (1) First, the sulfonated polymer-encapsulated carbon nanotube catalyst was synthesized: 3.2 g of sodium p-styrene sulfonate was dissolved in 19.6 mL of tetrahydrofuran and 4.5 mL of deionized water; after the sodium p-styrene sulfonate was completely dissolved, 0.4 g of carbon nanotubes were added, and the mixture was stirred at room temperature for 5 min; then 2.0 g of divinylbenzene was added, and the mixture was stirred at room temperature for 5 min; then 0.055 g of azobisisobutyronitrile was added, and the mixture was stirred for another 20 min. The rotor was removed, and a polytetrafluoroethylene liner was placed in the reactor; the reaction was carried out hydrothermally at 100 °C for 24 h; after the reaction was completed, the material was washed 5 times with methanol, 5 times with 1 mol / L sulfuric acid solution, and then 5 times with methanol. The material was then vacuum dried at 80 °C for 24 h. The solid material was ground into powder to obtain the sulfonated polymer-encapsulated carbon nanotube catalyst, named SPSS / DVB / CNT.
[0055] (2) Reaction conditions: 20 mg catalyst (SPSS / DVB / CNT), 1 mL DMSO, fructose mass concentration 31.3%, Fresnel lens, magnetic stirrer, natural sunlight, reaction time 10 minutes.
[0056] (3) After the reaction, dilute with water 5000 times, filter, and then put into a sample vial. HMF is determined by high performance liquid chromatography equipped with a UV detector, with a mobile phase of a mixture of methanol and water (V... 甲醇 V 水 = 60:40), column temperature 30℃. Fructose concentration was determined by high performance liquid chromatography equipped with a parallax detector, mobile phase 5 mM H2SO4, column temperature 35℃.
[0057] (4) In a high fructose concentration of 31.3%, under outdoor light irradiation for 10 minutes, the HMF yield of SPSS / DVB / CNT reached 85.2%, and the HMF generation rate per unit mass of the catalytic system per unit time was 8.9 mmol / L g. -1 h -1 Its corresponding TOF value is 307h -1 The above two indicators are superior to existing catalytic systems, including photothermal catalytic systems. Experimental results are shown in […]. Figure 6 See Table 1.
[0058] Table 1. Summary of the catalytic performance of SPSS / DVB / CNT catalysts for the conversion of fructose to HMF. 0.5 1 mL DMSO <![CDATA[Xenon lamp light source (1100 mW / cm 2 ), 45 min]]> 79.5 112.5 1.8 1.0 1 mL DMSO <![CDATA[Xenon lamp light source (2100 mW / cm 2 ), 10 min]]> 79.5 391.1 8.1 0.5 1 mL DMSO Natural sunlight + condenser lens, 10 min 85.2 307.0 8.9 Example
[0059] This invention discloses a method for encapsulating carbon materials with sulfonated polymers for photothermal catalysis, comprising the following steps: (1) First, the sulfonated polymer-encapsulated carbon nanotube catalyst was synthesized: 3.2 g of sodium p-styrene sulfonate was dissolved in 19.6 mL of tetrahydrofuran and 4.5 mL of deionized water; after the sodium p-styrene sulfonate was completely dissolved, 0.4 g of carbon nanotubes were added and stirred at room temperature for 5 min; 2.0 g of divinylbenzene was added and stirred at room temperature for 5 min; 0.055 g of azobisisobutyronitrile was added and stirred for 20 min. The rotor was removed and the polytetrafluoroethylene liner was placed in the reactor; the reaction was carried out at 100℃ for 24 h; after the reaction was completed, the material was washed 5 times with methanol, 5 times with 1 mol / L sulfuric acid solution, and then washed 5 times with methanol. The material was dried under vacuum at 80℃ for 24 h. The solid material was ground into powder to obtain the sulfonated polymer-encapsulated carbon nanotube catalyst, named SPSS / DVB / CNT.
[0060] (2) Reaction conditions: 20 mg catalyst (SPSS / DVB / CNT), different solvents, fructose 45-1000 g / L, reaction light intensity 1100 mW / cm 2 The reaction time is 5 to 120 minutes.
[0061] (3) After the reaction, the solution was diluted with water, filtered, and then placed into a sample vial. HMF was determined by high-performance liquid chromatography equipped with a UV detector, with a mobile phase of a mixture of methanol and water (V). 甲醇 V 水 = 60:40), column temperature 30℃.
[0062] (4) When the fructose concentration was 45 g / L, the catalytic effect experiment results showed that when the solvent was V γ-戊内酯 V 水 When the solvent ratio was 9:1, after 20 minutes of illumination, the HMF yield of SPSS / DVB / CNT reached as high as 73.3%; when the solvent was V... 四氢呋喃 V DMSO When the solvent ratio is 7:3, the HMF yield of SPSS / DVB / CNT reaches 77% after 90 minutes of illumination; when the solvent is only 1-butyl-3-methylimidazolium bromide (BMIMBr), the HMF yield of SPSS / DVB / CNT reaches 97% after 15 minutes of illumination; when the solvent is only 1-butyl-3-methylimidazolium bromide (BMIMBr), the HMF yield of SPSS / DVB / CNT reaches 96.6% after 15 minutes of illumination; when the solvent is only 1-butyl-3-methylimidazolium chloride (BMIMCl), the HMF yield of SPSS / DVB / CNT reaches 98.4% after 15 minutes of illumination. When the fructose concentration was 1000 g / L and the solvent was only 1-butyl-3-methylimidazolium chloride (BMIMCl), the HMF yield of SPSS / DVB / CNT was as high as 67.1%, 74.1%, and 78.4% after 5, 10, and 15 minutes of illumination, respectively. Example
[0063] This invention discloses a method for encapsulating carbon materials with sulfonated polymers for photothermal catalysis, comprising the following steps: (1) First, the sulfonated polymer-encapsulated carbon nanotube catalyst was synthesized: 3.2 g of sodium p-styrene sulfonate was dissolved in 19.6 mL of tetrahydrofuran and 4.5 mL of deionized water; after the sodium p-styrene sulfonate was completely dissolved, 0.4 g of carbon nanotubes were added and stirred at room temperature for 5 min; 2.0 g of divinylbenzene was added and stirred at room temperature for 5 min; 0.055 g of azobisisobutyronitrile was added and stirred for 20 min. The rotor was removed and the polytetrafluoroethylene liner was placed in the reactor; the reaction was carried out at 100℃ for 24 h; after the reaction was completed, the material was washed 5 times with methanol, 5 times with 1 mol / L sulfuric acid solution, and then washed 5 times with methanol. The material was dried under vacuum at 80℃ for 24 h. The solid material was ground into powder to obtain the sulfonated polymer-encapsulated carbon nanotube catalyst, named SPSS / DVB / CNT.
[0064] (2) Reaction conditions: 20 mg catalyst (SPSS / DVB / CNT), 1 mL DMSO, 500 mg inulin, reaction light intensity 2100 mW / cm 2 The reaction time is 1.5 to 30 minutes.
[0065] (3) After the reaction, dilute with water 5000 times, filter, and then put into a sample vial. HMF is determined by high performance liquid chromatography equipped with a UV detector, with a mobile phase of a mixture of methanol and water (V... 甲醇 V 水 = 60:40), column temperature 30℃.
[0066] (4) The experimental results of the catalytic effect show that 2100 mW / cm 2 At that time, in the inulin-DMSO system of 500 g / L, the HMF yield of SPSS / DVB / CNT was still as high as 69.0%, and the catalytic effect was shown in [reference needed]. Figure 10 . Example
[0067] This invention discloses a method for encapsulating carbon materials with sulfonated polymers for photothermal catalysis, comprising the following steps: First, a sulfonated polymer-encapsulated carbon nanotube catalyst was synthesized: 3.2 g of sodium p-styrene sulfonate was dissolved in 19.6 mL of tetrahydrofuran and 4.5 mL of deionized water; after the sodium p-styrene sulfonate was completely dissolved, 0.4 g of carbon nanotubes were added, and the mixture was stirred at room temperature for 5 min; then 2.0 g of divinylbenzene was added, and the mixture was stirred at room temperature for 5 min; then 0.055 g of azobisisobutyronitrile was added, and the mixture was stirred for another 20 min. The rotor was removed, and a polytetrafluoroethylene liner was placed in the reactor; the reaction was carried out hydrothermally at 100 °C for 24 h; after the reaction was completed, the material was washed 5 times with methanol, 5 times with 1 mol / L sulfuric acid solution, and then 5 times with methanol. The material was then vacuum dried at 80 °C for 24 h. The solid material was ground into powder, which is the sulfonated polymer-encapsulated carbon nanotube catalyst, named SPSS / DVB / CNT.
[0068] Preparation of glucose isomer catalyst: 1 g of P123 and 1.15 g (10 mmol) of H3PO4 were dissolved in 15 g of water and stirred for 2 h. 3.5 g (10 mmol) of SnCl4·5H2O was dissolved in 5 g of water and then added to the above H3PO4 solution. A white colloidal precipitate slowly formed. After stirring for 3 h, the resulting colloidal substance was transferred to a polypropylene bottle and placed in an oven at 100 °C for 72 h. After the reaction was complete, the sample was washed with deionized water and ethanol, respectively. The dried sample was SnP.
[0069] (3) Reaction conditions: 20 mg SPSS / DVB / CNT, 50 mg SnP, 1 mL DMSO, 10 mg inulin, reaction light intensity 1900 mW / cm 2 The reaction time is 15 to 90 minutes.
[0070] (4) After the reaction, dilute with water 500 times, filter, and then put into a sample vial. HMF is determined by high performance liquid chromatography equipped with a UV detector, with a mobile phase of a mixture of methanol and water (V). 甲醇 V 水 = 60:40), column temperature 30℃.
[0071] (5) The catalytic effect experimental results show that 1900 mW / cm 2 At that time, in a 10 g / L glucose-DMSO system, the highest yield of HMF was 54.1%, and the catalytic effect is shown in [reference needed]. Figure 11 . Example
[0072] This invention discloses a method for encapsulating carbon materials with sulfonated polymers for photothermal catalysis: (1) First, the sulfonated polymer-encapsulated carbon black catalyst was synthesized: 3.2 g of sodium p-styrene sulfonate was dissolved in 19.6 mL of tetrahydrofuran and 4.5 mL of deionized water; after the sodium p-styrene sulfonate was completely dissolved, 0.4 g of carbon black was added and stirred at room temperature for 5 min; 2.0 g of divinylbenzene was added and stirred at room temperature for 5 min; 0.055 g of azobisisobutyronitrile was added and stirred for 20 min. The rotor was removed and the polytetrafluoroethylene liner was placed in the reactor; the reaction was carried out at 100℃ for 24 h; after the reaction was completed, the material was washed 5 times with methanol, 5 times with 1 mol / L sulfuric acid solution, and then washed 5 times with methanol. The material was dried under vacuum at 80℃ for 24 h. The solid material was ground into powder to obtain the sulfonated polymer-encapsulated carbon black catalyst, named SPSS / DVB / CB.
[0073] (2) Reaction conditions: 20 mg catalyst (SPSS / DVB / CB), 1 mL DMSO, fructose concentration 3.9%, reaction light intensity 1100 mW / cm² 2 The reaction time is 15 to 90 minutes.
[0074] (3) After the reaction, dilute with water 5000 times, filter, and then put into a sample vial. HMF is determined by high performance liquid chromatography equipped with a UV detector, with a mobile phase of a mixture of methanol and water (V... 甲醇 V 水 = 60:40), column temperature 30℃. Fructose concentration was determined by high performance liquid chromatography equipped with a parallax detector, mobile phase 5 mM H2SO4, column temperature 35℃.
[0075] (4) In a 45 g / L fructose-DMSO solution, 1100 mW / cm 2 Under light irradiation for 15, 30, 60, and 90 minutes, the HMF yields of SPSS / DVB / CB were 80.5%, respectively. The catalytic effect is shown in [reference needed]. Figure 12 .
Claims
1. A method for encapsulating carbon materials with sulfonated polymers for photothermal catalysis, characterized in that, Step 5, start the reaction: After stirring for a certain period of time, remove the rotor and use sodium p-styrene sulfonate, carbon material and divinylbenzene as raw materials to synthesize a polymer-encapsulated carbon material. This polymer-encapsulated carbon material can catalyze the preparation of 5-hydroxymethylfurfural from fructose in dimethyl sulfoxide and can catalyze the preparation of furan compounds from fructose in ethanol.
2. A method for encapsulating carbon materials with sulfonated polymers for photothermal catalysis as described in claim 1, characterized in that, The synthesis steps for polymer-encapsulated carbon materials are as follows: Step 1, dissolving monomers: Add a certain volume of tetrahydrofuran and water to the lining of the polytetrafluoroethylene reactor, and add the weighed sodium p-styrene sulfonate to the solvent under stirring conditions; Step 2, introduce the crosslinking agent: add divinylbenzene after sodium p-styrene sulfonate has completely dissolved; Step 3, Add carbon material: After sodium styrene sulfonate and divinylbenzene are mixed evenly, add the carbon material. Step 4, Add initiator: After stirring for a certain period of time, add the initiator azobisisobutyronitrile (AIBN). Step 5, start the reaction: After stirring for a certain period of time, remove the rotor and put the polytetrafluoroethylene liner into the reactor. Perform a hydrothermal reaction at 100°C for 24 hours. Step 6, Cleaning and drying the materials: After the reaction is complete, wash the materials 5 times with methanol, then 5 times with sulfuric acid solution at 1 mol / L, then 5 times with methanol, and dry them under vacuum at 80 degrees Celsius for 24 hours. Finally, grind the solid material into powder, which is the catalyst.
3. A method for encapsulating carbon materials with sulfonated polymers for photothermal catalysis as described in claim 1, characterized in that, The preferred raw material ratio is 320 parts sodium p-styrene sulfonate, 40 parts carbon material, 200 parts divinylbenzene, 5.5 parts azobisisobutyronitrile, 174 parts tetrahydrofuran, and 45 parts water.
4. A method for encapsulating carbon materials with sulfonated polymers for photothermal catalysis as described in claim 1, characterized in that, The preparation of 5-hydroxymethylfurfural was achieved by polymer-encapsulated carbon nanotubes in dimethyl sulfoxide solvent via efficient catalysis. The preferred reaction conditions were: 4 parts catalyst, 9–200 parts fructose, 220 parts dimethyl sulfoxide, and a light intensity of 500–2100 mW / cm². 2 The reaction time is 5–120 minutes; the efficient catalytic preparation of furan compounds from fructose in anhydrous ethanol solvent is achieved under the following optimal reaction conditions: 4 parts catalyst, 9 parts fructose, 160 parts anhydrous ethanol, and light intensity of 900–1400 mW / cm². 2 The reaction time is 30 to 210 minutes.